Incorporation of Fluconazole and Ocimum Sanctum Oil in Soft Denture Liners to Treat Biofilms of Candida albicans Associated with Denture Stomatitis - Aamir Zahid Godil; Diksha Bhagat; Parijat Das; Ashi Ilyas Kazi; Ramandeep Dugal; Surekha Satpute (University Library System, University of Pittsburgh, 2021)
Purpose: To investigate the In Vitro activity of incorporated antifungal agents like Fluconazole and Ocimum sanctum oil (Tulsi) in the denture soft liners to reduce the risks associated with the biofilms of Candida albicans. Materials and Methods: In the current study, the minimum inhibitory concentration (MIC) of two antifungal agents namely Fluconazole and O. sanctum (Tulsi oil) against C. albicans (ATCC 10231) was evaluated to examine their effect in reducing the count of candida and its biofilms. Analysis of physical properties such as surface roughness and hardness of soft denture liners (test and control) were also performed. The effect of both antifungal agents was also observed on cell morphology of candida cells using scanning electron microscopy (SEM). Results: Studies confirmed MIC value for fluconazole and O. sanctum oil as 600 and 400 µg/ml respectively. Surface hardness and roughness of soft denture material (test) remained unaltered. Finally, SEM studies also proved the effectiveness of incorporated antifungal agents on the cell morphology of C. albicans at their respective MIC values. Conclusions: This approach allows the prolonged drug release in the oral cavity which simultaneously treats the injured denture bearing tissues and also the infection, biofilms of candida without compromising on their physical properties. These studies are significant and have tremendous medicinal and therapeutic relevance.